Improving Use of Medicines: Implementation of an Essential Medicines Policy in Public Health Facilities in Delhi (India). (December 2014) - Roy, Vandana; Gupta, Usha
In 1994 the Government of Delhi (India) implemented an essential medicines policy in public health facilities (HF) to improve the availability and rational use of medicines (RUM). An essential medicines list (EML) was made. Training programmes in RUM were initiated. After 13 years the outcome of the policy on RUM within public HF was evaluated.  Policy implementation improved the availability of medicines to 91.4 per cent. Prescribing of medicines from EML increased (94.6 per cent) and antimicrobials declined (51.7 per cent). The number of patients with complete knowledge of how to take prescribed medicines improved (53.4 per cent). However, the use of generic medicines declined (18.1 per cent) and prescriptions were mostly incomplete (79.6 percent).  Majority of prescribers lacked awareness about the Drug Policy, including not having undergone training sessions on RUM. There were no Drugs and Therapeutic Committees within HF, and only a few doctors had information about medicines available within the HF. The most common sources of information for medicines were commercial published sources and medical representatives of pharmaceutical companies.  The regulatory intervention of enforcing an EML in public HF has been successful in increasing the use of medicines from the EML and improving some prescribing indicators. However, educational interventions have been inadequate and need to be combined and strengthened to improve the policy outcomes in RUM.